Assessment of Women Participation in Rice Production value Chain in Cross River State, Nigeria - Effiong, John Ben; David, Goodness Mosiokpahe (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
With an emphasis on identifying the barriers women encounter in rice production activities, this study evaluates their involvement in the value chain of rice production in Cross River State, Nigeria. The three agricultural zones in the state that are actively involved in the rice value chain were the sites of the investigation. 284 women in all were chosen from different blocks and cells within the zones using a multi-stage sampling technique. The study aimed to ascertain the level of women’s involvement in rice production and highlight the factors hindering their participation. Findings revealed that most women sourced rice seeds from local markets (56.1%) and previous harvests (39.2%), with limited access to improved seed varieties or extension services. Additionally, women primarily engaged in manual rice production activities, with very few using mechanized methods. The study further identified key constraints affecting women’s participation, including the high cost of fuel (ranked 1st), poor access to credit (2nd), illiteracy (3rd), inadequate training (4th), and limited access to extension services (5th). These constraints were found to significantly impede their ability to engage in large-scale rice production. The lack of mechanization and insufficient technical support were particularly limiting factors. The findings demonstrated how important fuel and loan availability are to raising women's participation and productivity in the rice value chain. The study comes to the conclusion that boosting women's participation in rice production requires tackling these obstacles with focused interventions, such as more inexpensive fuel, better finance availability, improved automation, and increased extension services. For women in Cross River State, these adjustments may result in increased economic empowerment, increased productivity, and better socioeconomic results. According to the report, policy changes are necessary to increase women's access to landed resources and guarantee their long-term involvement in agricultural value chains.